Monitoring Pemberian Obat Cacing pada Sapi Potong di Desa Selebung Kecamatan Janapria Lombok Tengah - Kholik; Candra Dwi Atma; Ismail Marzuki; Iwan Desimal; Syafindri (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Helminthiasis is still a problem in the beef cattle business in Slebung Village, Janapria District, Central Lombok Regency. The purpose of this service activity is to provide farmers with knowledge about helminthiasis, the procedure for administering worm medicine, and monitoring the effectiveness of deworming in beef cattle. This service is carried out with counseling preceded by surveys and interviews with the village head and practice in the cages of breeders who become pilot models. The worm medicine given is Albendazole which will be monitored for 14 days by maintaining the Covid-19 Health protocol. Monitoring the effectiveness of deworming was assessed based on the number of worm eggs per gram of feces or Eggs Per Gram (EPG) of Feces and the value of the Fecal Egg Count Reduction Test (FECRT) which was examined by the Mc Master method. The results of the examination showed that the value of Eggs Per Gram (EPG) of Feces before (pre) and after (post) administration of worm medicine to beef cattle with helminthiasis decreased from 110.00 ± 62.34 to 16.66 ± 8 with a percentage value of FECRT is 85%.